The emergence of Aegean prehistory - Shapland, Andrew (Cambridge elements, 2025)
This Element focusses on the emergence of Aegean Prehistory as a discipline, starting with the first recorded encounters with prehistoric monuments and artefacts and ending with the decipherment of Linear B in 1952. It broadens the history of Aegean Bronze Age archaeology as told in popular accounts as a series of excavations of great men, particularly Heinrich Schliemann at Troy and Mycenae and Sir Arthur Evans at Knossos. Though their work is of fundamental importance for the discipline, here it is placed within wider political, institutional and intellectual frameworks. This Element also provides an overview of the work of many other archaeologists across the Aegean and the regional and historical context in which they operated. It provides a brief but comprehensive history of the formative stages of the study of Aegean Prehistory